The Effect of Flow Rate and NaCl Concentration on the Corrosion Behavior of Carbon Steel in NaCl Solutions Containing H2S. Issue 1 (April 2020) - Dwi Rachmawati, Indah; Nurdin, Isdiriayani; Widiatmoko, Pramujo; Devianto, Hary; Irmayanti, Festi; Saptohadi, Samuel
Abstract: Most of components in industry are made of carbon steel which has low corrosion resistance. Therefore, the industry's equipment is highly susceptible to corrosion. This study is focused on the characterization of carbon steel corrosion in flowing NaCl solutions with H2 S impurities. The corrosion rate was measured by using potentiostat. H2 S gas was generated from the Kipp apparatus to produce a concentration of 600 ppm. The NaCl concentration was varied at 50, 40, 000, and 60, 000 ppm. The flow rate was varied at 0.5, 2.3 and 4.1 ft/s by utilizing a Rotating Disk Electrode (RDE). Corrosion mechanism was predicted by utilizing Cyclic Voltammetry (CV), Electrochemical Impedance Spectroscopy (EIS), and confirmed by analysing the composition of the corrosion product using X-ray Diffraction (XRD), and Scanning Electron Microscope (SEM). The experimental results indicate that the breakaway velocity for NaCl solutions containing H2 S of 600 ppm are around 4, 500 rpm. At low level conductivity, corrosion rate increases as NaCl concentration increases. Then, after reaching 40, 000 ppm, NaCl corrosion rate decreases along with the increase of NaCl concentration. The flow rate, NaCl concentration, and interaction between both variables are influential variable for corrosion rate. There is antagonistic influent to corrosion rate at 1000 rpm flow rate, 50 ppm NaCl, and 60, 000 ppm NaCl.